Manliness in Britain, 1760-1900 : bodies, emotion, and material culture - Begiato, Joanne (Studies in design and material culture., 2020)
This book focuses on men's bodies, emotions and material culture to offer a new understanding of masculinities in Britain in the long nineteenth century. Using objects as well as texts and images, it shows how idealised and ugly bodies, and the feelings they stimulated, helped convey ideas about manliness and unmanliness across society.